(untitled) (Texas Journal of Medical Science, 2023)
Tracheostomy is a description of the surgical opening of the trachea, and represents the most frequently carried out surgical procedures in medical practice, especially in patients who require long-term mechanical ventilation for airway disorders. This study aimed to evaluate the main indications for tracheostomy. Approximately 100 patients underwent tracheostomy in different age groups, from 12 to 80 years, and both genders, who attended Baquba Teaching Hospital, (Iraq) in the period from August 2021 to December 2022, were included in this cross-sectional study. The results showed that the indications for tracheostomy were due to prolonged ventilation (70%) resulting from trauma in most cases (71.5%), followed by upper airway obstruction (25%) due to tumors (40%) or trauma (60%). As for the rest (5%), it was from other procedures such as maxillofacial injuries. It was concluded that prolonged ventilation due to trauma was the most common indication for tracheostomy in Baquba Teaching Hospital